Resting autonomic nervous system activity is unrelated to antisocial behaviour dimensions in adolescents: Cross-sectional findings from a European multi-centre study. (November 2019) - Prätzlich, Martin; Oldenhof, Helena; Steppan, Martin; Ackermann, Katharina; Baker, Rosalind; Batchelor, Molly; Baumann, Sarah; Bernhard, Anka; Clanton, Roberta; Dikeos, Dimitris; Dochnal, Roberta; Fehlbaum, Lynn Valérie; et al.
Abstract: Purpose: Autonomic nervous system (ANS) functioning has long been studied in relation to antisocial behaviour, but relevant measures (heart rate, heart rate variability, pre-ejection period, respiration rate) have rarely been considered together. This study investigated the relationship between these measures and antisocial behaviour. Methods: Using a sample of 1010 youths with (47.8%) and without conduct disorder (52.2%) aged between 9 and 18 years (659 females, 351 males, mean age = 14.2 years, SD = 2.4), principal component analysis (PCA) was applied to various measures of psychopathology and antisocial behavior. Structural equation modelling was performed in order to test whether the ANS measures predicted PCA-dimensions. Cluster analysis was used in order to classify patterns of ANS activity. Analyses were performed separately for males/females and controlled for body-mass-index, age, caffeine use, cigarette smoking, sports, socioeconomic status, medication, cardiac problems. Results: The PCA yielded three components: antisocial behaviour/comorbid psychopathology, narcissistic traits, and callous-unemotional traits. ANS measures were only weakly correlated with these components. Cluster analysis yielded high and low arousal clusters in both sexes. When controlling for covariates, all associations disappeared. Conclusion: Our findings suggest that resting ANS measures are only weakly related to antisocial behaviour and indicate that smoking should be considered as an important covariate in future psychophysiological studies. Highlights: Respiration rate and antisocial behaviour were positively associated in females. Covariates rendered links between the ANS and antisocial behaviour non-significant. For both sexes, a low and a high arousal cluster arose. Smoking was strongly related to antisocial behaviour and comorbid psychopathology.